Biomaterials in skin tissue engineering. Issue 13 (2nd September 2022) - Wei, Chao; Feng, Yihua; Che, Dezhao; Zhang, Jiahui; Zhou, Xuan; Shi, Yanbin; Wang, Li
Abstract: Wounds affect various functions of the skin, and treating them has always been a challenge for humans. Skin grafts have been traditionally used to treat wounds; however, they have certain shortcomings. Skin tissue engineering has many advantages, and thus, it is expected to become a new method for wound treatment. Suitable skin substitutes are necessary for skin tissue engineering, and the materials of the scaffolds affect the properties of skin substitutes. Only suitable materials can promote wound healing, so it is very important to choose the right materials and study their characteristics for skin tissue engineering. This article reviews scaffold materials, including natural, synthetic, and composite materials, and their advantages, disadvantages are analyzed. In addition, this review presents current commercially available skin substitutes for clinical use. Finally, the perspectives and existing challenges in the field of skin tissue engineering are presented. Graphical Abstract: UF0001